2013
DOI: 10.1002/oby.20433
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double‐blind placebo‐controlled study of leptin administration after gastric bypass

Abstract: Objective Obese individuals have high levels of circulating leptin and are resistant to the weight-reducing effect of leptin administration at physiological doses. Although Roux-en-Y gastric bypass (RYGB) is an effective weight loss procedure, there is a plateau in weight loss and most individuals remain obese. This plateau may be partly due to the decline in leptin resulting in a state of relative leptin insufficiency. The main objective of this study was to determine whether leptin administration to post-RYG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 41 publications
(63 reference statements)
3
29
0
Order By: Relevance
“…No difference in the weight change was observed between the groups at the end of 8 weeks of treatment. Furthermore, no changes were noted in either thyroid hormone or cortisol levels (Korner et al 2013).…”
Section: Leptin For Weight-loss Maintenance In Obesitymentioning
confidence: 82%
“…No difference in the weight change was observed between the groups at the end of 8 weeks of treatment. Furthermore, no changes were noted in either thyroid hormone or cortisol levels (Korner et al 2013).…”
Section: Leptin For Weight-loss Maintenance In Obesitymentioning
confidence: 82%
“…We previously reported that, contrary to our expectation, leptin administration did not lead to further weight loss in women who had undergone weight loss after RYGB and whose leptin levels were lower than that predicted for a nonreduced individual with the same BMI [32]. This paper examines our secondary objective, which was to establish whether leptin administration in this weight-reduced state would be associated with changes in hormones involved in nutrient metabolism as well as in satiation.…”
Section: Introductionmentioning
confidence: 89%
“…In the first randomized placebo-controlled double-blind dose-escalation trial of 54 lean and 73 obese participants, significant weight loss was observed in obese participants on metreleptin versus placebo, with the greatest difference being 1.7 kg on placebo and 7.1 kg on 0.30 mg/ kg/d dosing [50]. Other trials, however, resulted in no significant effect of metreleptin on weight loss, though studies varied by population (weight, co-morbidities) [56], serum leptin concentration [66--68], and mode of weight loss [69]. On the other hand, the pramlintide/metreleptin study showed a synergistic effect on weight loss with~13% weight loss with dual therapy versus~5% weight loss with each drug alone [59].…”
Section: Expert Opinionmentioning
confidence: 96%